C3N4 sheet loaded metal nano material embedded into carbon holes and preparation method of C3N4 sheet loaded metal nano material
By loading and embedded metal nanoparticles with porous carbon materials on the C3N4 sheet layer, the size of metal nanoparticles is regulated by the limiting effect of carbon pores, the problem of insufficient activity and stability of metal catalysts in the prior art is solved, and efficient catalytic activity improvement and the reduction of precious metal demand are achieved.
Patent Information
- Application Number
- CN202411864875.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively regulate the electronic structure of metals and improve metal-support interactions, resulting in insufficient catalytic activity and stability of metal catalysts.
By loading metal nanoparticles on the C3N4 sheet layer and embedding them into the pores of porous carbon material, the size of metal nanoparticles is regulated using the domain-limiting effect of carbon pores, thereby improving metal-support interaction and catalytic activity.
The catalytic activity and stability of metal catalysts are improved, while reducing the demand for precious metals. The preparation method is simple and has good actual production value.
Smart Images

Figure CN119685876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano metal materials, and in particular relates to a C3N4 sheet-loaded metal nano material embedded in carbon pores and a preparation method thereof. Background Art
[0002] The carrier of a supported metal catalyst often plays not only the role of stabilizing and dispersing metal particles, but also plays a role in affecting the activity, selectivity and stability of the catalyst in terms of charge transfer at the interface and changes in the metal structure. This effect is called metal-carrier interaction. g-C3N4 is a nitrogen-containing graphene-like structural material that can evenly disperse metal particles on the surface and anchor them through N-metal bonds. This metal-carrier interaction promotes charge transfer, inhibits the aggregation and shedding of metal particles, and thus greatly enhances the catalytic activity and stability. Studies have shown that ultra-thin C3N4 sheets can exhibit super strong catalytic activity and stability. The excellent performance it exhibits is the result of the synergistic cooperation of its advantages such as large specific surface area and many reactive active sites. However, most of the reported literature adopts a top-down strategy, that is, first prepare a bulk C3N4 with a complete crystal structure and then peel it off. This is undoubtedly a complex, time-consuming and expensive method. At the same time, due to the weak hydrogen bonds between C3N4 layers, the planar atomic structure will be seriously unbalanced, resulting in unfavorable defects.
[0003] Therefore, how to further regulate the electronic structure of metals, improve the metal-support interaction, and enhance its intrinsic catalytic ability remains a difficult problem. Studies have shown that the size of metal nanoparticles can be effectively limited by confinement. Therefore, if the technology of confined metal nanoparticles can be introduced into the preparation of metal-C3N4, the resulting C3N4 sheets embedded in carbon pores and loaded with metal nanomaterials may exhibit higher catalytic activity and stability. However, there are currently no reports on C3N4 sheets embedded in carbon pores and loaded with metal nanomaterials in the world, and the effect of the introduction of ultra-thin C3N4 formed by the confinement effect on the activity and stability of metal nanomaterials is still unknown. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores and a preparation method thereof, so as to improve the metal-carrier interaction and enhance the catalytic ability of the metal nanocatalyst.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The present invention provides a C3N4 sheet-loaded metal nanomaterial embedded in carbon pores, the material comprises C3N4, metal nanoparticles and porous carbon material, the metal nanoparticles are loaded on the C3N4 sheet layer and then embedded in the pores of the porous carbon material; based on the total weight of the material, the mass percentage of the metal nanoparticles is 0.1% to 70%; the molar ratio of C3N4 to the metal nanoparticles is 1:(0.01 to 1). The mass percentage of the metal nanoparticles is preferably 1% to 30%, and more preferably 2% to 10%.
[0007] Furthermore, the metal is selected from at least one of noble metals and transition metals; and the porous carbon material is selected from any one of natural carbon materials, artificial carbon materials, or various types of derived carbon materials, such as conductive carbon black.
[0008] Furthermore, the precious metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, silver, and osmium; and the transition metal is selected from at least one of iron, cobalt, copper, nickel, manganese, molybdenum, chromium, tungsten, zinc, and bismuth.
[0009] Furthermore, the size of the metal nanoparticles is 1 nm to 50 nm. Preferably, the size of the metal nanoparticles is 3 nm to 5 nm.
[0010] The present invention also provides a method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores as described above, comprising the following steps: mixing a porous carbon material, a metal salt precursor and a nitrogen-containing precursor, subjecting the mixture to a high-temperature roasting process, and then cooling the mixture to room temperature to obtain a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores.
[0011] Further, the metal salt precursor is at least one of a noble metal precursor or a transition metal salt precursor; the noble metal precursor is selected from at least one of a noble metal acid, a noble metal chloride or a noble metal nitrate; the transition metal salt precursor is selected from at least one of a transition metal sulfate, a transition metal chloride, a transition metal acetate and a transition metal nitrate;
[0012] The nitrogen-containing precursor is selected from at least one of polypyrrole, polyaniline, polythiophene, polydopamine, pyrrole, aniline, pyridine, polypyridine, triethylenetetramine, porphyrin, phthalocyanine, o-phenanthroline, imidazole, dopamine, thiophene, ethylenediamine, thiourea, cyanamide, dicyandiamide, urea or melamine.
[0013] Furthermore, the porous carbon material, the metal salt precursor and the nitrogen-containing precursor are mixed evenly by impregnation mixing or ultrasonic mixing; the solvent used in the impregnation mixing or ultrasonic mixing is selected from any one of methanol, ethanol, acetone, ethylene glycol or isopropanol.
[0014] Furthermore, the conditions of the high temperature calcination process are: calcination at 400° C. to 600° C. for 0.5 h to 48 h in a specific atmosphere.
[0015] Furthermore, the specific atmosphere is selected from any one of argon, nitrogen, helium, hydrogen-nitrogen mixture, hydrogen-argon mixture, hydrogen-helium mixture, carbon monoxide-nitrogen mixture, carbon monoxide-helium mixture, hydrogen or carbon monoxide; the volume concentration of hydrogen or carbon monoxide in the mixture is 0.1% to 30%.
[0016] Furthermore, the cooling to room temperature adopts any one of natural cooling, rapid cooling or programmed cooling; wherein the cooling rate of the rapid cooling method is 30°C / min to 60°C / min; the cooling rate of the programmed cooling method is 0.5°C / min to 20°C / min.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention provides a C3N4 sheet-loaded metal nanomaterial embedded in carbon pores and a preparation method thereof. By introducing C3N4 sheets, the metal-carrier interaction is improved and the intrinsic catalytic ability of the metal is regulated, thereby improving the catalytic activity of the metal catalyst while reducing the demand for precious metals.
[0019] (2) The present invention provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores and a preparation method thereof, which can regulate the size of metal nanoparticles and increase the active area through the confinement effect of carbon pores, thereby improving the catalytic activity of the metal catalyst.
[0020] (3) The preparation method of the C3N4 sheet loaded with metal nanomaterials embedded in carbon pores of the present invention is simple, and suitable process conditions can be selected for the mixing, calcination, cooling and other processes to achieve the best preparation effect, which has good practical production value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD pattern of the Ru-C3N4 / C nanomaterial prepared in Example 1 of the present invention;
[0022] Figure 2 TEM image of the Ru-C3N4 / C nanomaterial prepared in Example 1 of the present invention;
[0023] Figure 3 LSV curves of Ru-C3N4 / C nanomaterial and Ru / C nanomaterial prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0025] The present invention provides a C3N4 sheet-loaded metal nanomaterial embedded in carbon pores, the material comprises C3N4, metal nanoparticles and porous carbon material, the metal nanoparticles are loaded on the C3N4 sheet layer and then embedded in the pores of the porous carbon material; based on the total weight of the material, the mass percentage of the metal nanoparticles is 0.1% to 70%; the molar ratio of C3N4 to the metal nanoparticles is 1:(0.01 to 1). The mass percentage of the metal nanoparticles is preferably 1% to 30%, and more preferably 2% to 10%. The size of the metal nanoparticles is 1nm to 50nm. Preferably, the size of the metal nanoparticles is 3nm to 5nm. The metal is selected from at least one of noble metals or transition metals; the noble metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, silver and osmium; the transition metal is selected from at least one of iron, cobalt, copper, nickel, manganese, molybdenum, chromium, tungsten, zinc and bismuth; the porous carbon material is selected from any one of natural carbon materials, artificial carbon materials or various types of derived carbon materials. For example, conductive carbon black, etc.
[0026] The C3N4 sheet loaded with metal nanomaterials embedded in carbon pores is prepared by the following method:
[0027] The porous carbon material, the metal salt precursor and the nitrogen-containing precursor are mixed and calcined at 400°C to 600°C for 0.5h to 48h in a specific atmosphere, and then cooled to room temperature to obtain the C3N4 sheet-loaded metal nanomaterial embedded in the carbon pores. The metal salt precursor is at least one of a noble metal precursor or a transition metal salt precursor; the noble metal precursor is selected from at least one of a noble metal acid, a noble metal chloride or a noble metal nitrate; the transition metal salt precursor is selected from at least one of a transition metal sulfate, a transition metal chloride, a transition metal acetate and a transition metal nitrate; the nitrogen-containing precursor is selected from at least one of polypyrrole, polyaniline, polythiophene, polydopamine, pyrrole, aniline, pyridine, polypyridine, triethylenetetramine, porphyrin, phthalocyanine, o-phenanthroline, imidazole, dopamine, thiophene, ethylenediamine, thiourea, cyanamide, dicyandiamide, urea or melamine.
[0028] In some specific embodiments, the porous carbon material, the metal salt precursor and the nitrogen-containing precursor are uniformly mixed by impregnation mixing or ultrasonic mixing; the solvent used in the impregnation mixing or ultrasonic mixing is selected from any one of methanol, ethanol, acetone, ethylene glycol or isopropanol.
[0029] In some specific embodiments, the specific atmosphere is selected from any one of argon, nitrogen, helium, hydrogen-nitrogen mixture, hydrogen-argon mixture, hydrogen-helium mixture, carbon monoxide-nitrogen mixture, carbon monoxide-helium mixture, hydrogen or carbon monoxide; the volume concentration of hydrogen or carbon monoxide in the mixture is 0.1% to 30%.
[0030] In some specific embodiments, the cooling to room temperature is carried out by any one of natural cooling, rapid cooling or programmed cooling; wherein the cooling rate of the rapid cooling method is 30°C / min to 60°C / min; the cooling rate of the programmed cooling method is 0.5°C / min to 20°C / min.
[0031] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0032] Comparative Example 1
[0033] This comparative example provides a Ru / C material, and the specific preparation steps are as follows:
[0034] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0065g of ruthenium trichloride trihydrate (RuCl3·3H2O), ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 500℃ for 2h under argon atmosphere at a heating rate of 2℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is Ru / C nanomaterial.
[0035] Example 1
[0036] This embodiment provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, wherein the metal is ruthenium (Ru), the nitrogen-containing precursor is urea, and the porous carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0037] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0065g of ruthenium trichloride trihydrate (RuCl3·3H2O) and 0.065g of urea, and ultrasonicate for 2h. The viscous sample is placed in a vacuum oven at 70℃ and dried for 12h. The solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 500℃ for 2h under argon atmosphere with a heating rate of 2℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Ru-C3N4 / C nanomaterial.
[0038] Figure 1 The XRD spectrum of the Ru-C3N4 / C nanomaterial prepared in Example 1 is compared with the PDF standard card (PDF#06-0663). Figure 1 The characteristic diffraction peak of Ru metal cannot be seen. Figure 2 TEM image of the Ru-C3N4 / C nanomaterial prepared in Example 1. Figure 2 It can be seen that the size of the metal nanoparticles in the Ru-C3N4 / C nanomaterial is 3-5nm. Combining the analysis of the two shows that Example 1 successfully loads Ru on the C3N4 sheet and embeds it into the pores of the carbon carrier; the C3N4 sheet stabilizes and disperses Ru, providing a structural basis for improving the metal-carrier interaction between Ru and Ru; at the same time, based on the confinement effect of the carbon pores, the size of the metal nanoparticles can be controlled and the active area is increased.
[0039] The above results indicate the successful preparation of Ru-C3N4 / C nanomaterials.
[0040] Example 2
[0041] This embodiment provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, wherein the metal is ruthenium (Ru), the nitrogen-containing precursor is urea, and the porous carbon carrier is conductive carbon black (specific model is Ketjenblack EC-300JD). The specific preparation method of this embodiment is as follows:
[0042] Take 0.05g Ketjenblack EC-300JD and place it in a mortar. Then add 0.0065g ruthenium trichloride trihydrate (RuCl3·3H2O) and 0.065g urea and other solids to the above Ketjenblack EC-300JD and grind for 30 minutes to obtain a mixed powder. The mixed powder is placed in a beaker containing 2mL of isopropanol and ultrasonically treated for 20 minutes. Then the solvent is evaporated to obtain a dry solid powder. The obtained solid mixed powder is moved to a tube furnace and calcined at 600℃ for 2h under a hydrogen atmosphere with a heating rate of 2℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is Ru-C3N4 / C nanomaterial.
[0043] Example 3
[0044] This embodiment provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, wherein the metal is ruthenium (Ru), the nitrogen-containing precursor is urea, and the porous carbon carrier is conductive carbon black (specific model is Vulcan XC-72). The specific preparation method of this embodiment is as follows:
[0045] 0.05g of Vulcan XC-72 was placed in a beaker containing 100ml of methanol and ultrasonically treated for 30min. Then, 0.0065g of ruthenium trichloride trihydrate (RuCl3·3H2O) and 0.65g of urea and other solids were added to the beaker and ultrasonicated for 30min. Then, the solvent was evaporated to obtain a dry solid powder. The obtained solid mixed powder was moved to a tube furnace and calcined at 500℃ for 24h in a carbon monoxide / nitrogen (10% CO / 90% N2) atmosphere at a heating rate of 2℃ / min, and then cooled to room temperature at a cooling rate of 2℃ / min. The obtained solid powder was Ru-C3N4 / C nanomaterial.
[0046] Example 4
[0047] This embodiment provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, wherein the metal is iridium (Ir), the nitrogen-containing precursor is polydopamine, and the porous carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0048] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0065g chloroiridic acid hydrate (H2Cl6Ir·xH2O) and 0.065g polydopamine, and ultrasonicate for 2h. The viscous sample is placed in a vacuum oven at 70℃ and dried for 12h. The solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 500℃ for 36h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere with a heating rate of 5℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Ir-C3N4 / C nanomaterial.
[0049] Example 5
[0050] This embodiment provides a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, wherein the metals are palladium (Pd) and iron (Fe), the nitrogen-containing precursor is ethylenediamine, and the porous carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0051] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0065g palladium chloride (PdCl2), 0.003g iron nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.065g ethylenediamine, and ultrasonicate for 2h. The viscous sample is placed in a vacuum oven at 70℃ and dried for 12h. The solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 500℃ for 36h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere with a heating rate of 5℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Pd-Fe-C3N4 / C nanomaterial.
[0052] According to the thermogravimetric analysis results, the contents of metal nanomaterial components loaded in the C3N4 sheets embedded in carbon pores obtained in Examples 1-5 are shown in Table 1.
[0053] Table 1 Content of metal nanomaterial components in C3N4 sheets embedded in carbon pores obtained in Examples 1-5
[0054] Mass percentage of metal nanoparticles <![CDATA[Molar ratio of C3N4 to metal nanoparticles]]> Comparative Example 1 4.78% 0 Example 1 4.35% 1 / 0.4398 Example 2 4.37% 1 / 0.4691 Example 3 2.56% 1 / 0.0503 Example 4 5.24% 1 / 0.2660 Example 5 7.25% 1 / 0.7800
[0055] The materials obtained in Example 1 and Comparative Example 1 were tested as follows:
[0056] A three-electrode test system was used, the electrolyte was 1M KOH, and the CHI-760E electrochemical station was used at room temperature. Platinum foil was used as the counter electrode and Hg / HgO was used as the reference electrode. The catalyst slurry was prepared using ultrapure water and ethanol (v / v = 50:950) and a certain amount of 5wt% Nafion solution. 20μL of the catalyst slurry was placed on a glassy carbon electrode (d = 5mm, with a geometric electrode area of 0.196cm 2 ) and dried in air to prepare a working electrode. For Example 1, the Ru loading on the electrode is 0.015 mg cm -2 For comparative example 1, the Ru loading is 0.015 mg cm -2 The polarization curve of hydrogen evolution reaction was obtained by linear sweep voltammetry (LSV) with a scan rate of 5 mVs -1 .
[0057] In the evaluation of the catalytic activity of hydrogen evolution reaction catalysts, the current density is generally 10 mA cm -2 The overpotential at which the catalyst is reacted is used to characterize and compare the performance of the catalyst. The standard potential of the hydrogen evolution reaction is 0 V, so the current density is 10 mA cm -2 The potential at which the catalyst reacts is called the overpotential. The smaller the overpotential, the better the hydrogen evolution reaction performance of the catalyst.
[0058] like Figure 3 As shown, Figure 3 Figure 1 is a polarization curve diagram of Ru-C3N4 / C prepared in Example 1 and Ru / C prepared in Comparative Example 1. Figure 3 The middle curve data shows that when Ru / C in Comparative Example 1 is used for hydrogen evolution reaction at a current density of 10 mA cm -2 The overpotential at the current density of 100 mA cm-2 was 35 mV, while the overpotential for the Ru-C3N4 / C material in Example 1 was only 22 mV. -2 The overpotential at reached 127 mV, while for the Ru-C3N4 / C material in Example 1, this value was only 98 mV, which indicates that the C3N4 sheets formed by the introduction of urea enhanced the metal-support interaction with Ru, thereby adjusting the electronic structure of Ru, and through the confinement effect of carbon pores, the size of metal nanoparticles (3-5 nm) was regulated, the active area was increased, and the intrinsic catalytic ability of metal Ru was enhanced, thereby effectively improving its catalytic activity as a hydrogen evolution reaction catalyst.
[0059] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A C3N4 sheet loaded with metal nanomaterials embedded in carbon pores, characterized in that: The material comprises C3N4, metal nanoparticles and porous carbon material, wherein the metal nanoparticles are loaded on the C3N4 sheet and then embedded in the pores of the porous carbon material; Based on the total weight of the material, the mass percentage of the metal nanoparticles is 0.1% to 70%; The molar ratio of C3N4 to metal nanoparticles is 1:(0.01~1).
2. The C3N4 sheet loaded with metal nanomaterial embedded in carbon pores according to claim 1, characterized in that: The metal is selected from at least one of a noble metal or a transition metal; The porous carbon material is selected from any one of natural carbon materials, artificial carbon materials or various types of derived carbon materials.
3. A C3N4 sheet loaded with metal nanomaterial embedded in carbon pores according to claim 2, characterized in that: The noble metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, silver and osmium; The transition metal is selected from at least one of iron, cobalt, copper, nickel, manganese, molybdenum, chromium, tungsten, zinc and bismuth.
4. The C3N4 sheet loaded with metal nanomaterial embedded in carbon pores according to claim 1, characterized in that: The size of the metal nanoparticles is 1nm to 50nm.
5. A method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing a porous carbon material, a metal salt precursor and a nitrogen-containing precursor, subjecting the mixture to a high-temperature calcination process, and then cooling the mixture to room temperature to obtain a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores.
6. The method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores according to claim 5, characterized in that: The metal salt precursor is at least one of a noble metal precursor or a transition metal salt precursor; The noble metal precursor is selected from at least one of noble metal acid, noble metal chloride or noble metal nitrate; the transition metal salt precursor is selected from at least one of transition metal sulfate, transition metal chloride, transition metal acetate and transition metal nitrate; The nitrogen-containing precursor is selected from at least one of polypyrrole, polyaniline, polythiophene, polydopamine, pyrrole, aniline, pyridine, polypyridine, triethylenetetramine, porphyrin, phthalocyanine, o-phenanthroline, imidazole, dopamine, thiophene, ethylenediamine, thiourea, cyanamide, dicyandiamide, urea or melamine.
7. The method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores according to claim 5, characterized in that: The porous carbon material, the metal salt precursor and the nitrogen-containing precursor are uniformly mixed by an impregnation mixing method or an ultrasonic mixing method; The solvent used in the immersion mixing method or the ultrasonic mixing method is selected from any one of methanol, ethanol, acetone, ethylene glycol or isopropanol.
8. The method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores according to claim 5, characterized in that: The conditions of the high temperature calcination process are: calcination at 400°C to 600°C for 0.5h to 48h in a specific atmosphere.
9. The method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores according to claim 8, characterized in that: The specific atmosphere is selected from any one of argon, nitrogen, helium, hydrogen-nitrogen mixture, hydrogen-argon mixture, hydrogen-helium mixture, carbon monoxide-nitrogen mixture, carbon monoxide-helium mixture, hydrogen or carbon monoxide; The volume concentration of hydrogen or carbon monoxide in the mixed gas is 0.1% to 30%.
10. The method for preparing a C3N4 sheet loaded with metal nanomaterials embedded in carbon pores according to claim 5, characterized in that: The cooling to room temperature is carried out by any one of natural cooling, rapid cooling or programmed cooling; Among them, the cooling rate of the rapid cooling method is 30℃ / min~60℃ / min; the cooling rate of the programmed cooling method is 0.5℃ / min~20℃ / min.